2016
DOI: 10.1136/bmjopen-2016-012386
|View full text |Cite
|
Sign up to set email alerts
|

Is poor oral health a risk marker for incident cardiovascular disease hospitalisation and all-cause mortality? Findings from 172 630 participants from the prospective 45 and Up Study

Abstract: ObjectiveTo investigate the relationship between oral health and incident hospitalisation for ischaemic heart disease (IHD), heart failure (HF), ischaemic stroke and peripheral vascular disease (PVD) and all-cause mortality.DesignProspective population-based study of Australian men and women aged 45 years or older, who were recruited to the 45 and Up Study between January 2006 and April 2009; baseline questionnaire data were linked to hospitalisations and deaths up to December 2011. Study exposures include too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 47 publications
(50 reference statements)
4
84
2
2
Order By: Relevance
“…Several studies have reported that having fewer teeth at baseline or losing teeth during study follow-up increases the risk of a range of adverse health outcomes. [1][2][3][4][5][6][7] While there is growing interest in tooth loss as an epidemiological measure of dental status, valid inference from these studies requires an understanding of what is represented by tooth loss.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that having fewer teeth at baseline or losing teeth during study follow-up increases the risk of a range of adverse health outcomes. [1][2][3][4][5][6][7] While there is growing interest in tooth loss as an epidemiological measure of dental status, valid inference from these studies requires an understanding of what is represented by tooth loss.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,[23][24][25][26] The results of this pilot project support the usefulness and applicability of oral health guidelines for this population. Because oral health is important for systemic health, [8][9][10][11][12] interventions that support oral health may have a positive impact on overall health in this population.…”
Section: Practicing Nurse Practitioners and Dental Hygienistsmentioning
confidence: 99%
“…Furthermore, individuals with PD are more likely to have difficulty retaining dentures, have an increased likelihood of cracked teeth and often suffer from orofacial pain, burning mouth syndrome and taste impairment . Poor OH is a risk factor for systemic diseases, including cardiovascular disease, diabetes and respiratory infections . Poor OH can also lead to poor nutrition, including decreased calorie intake and nutrient intake and a decreased quality of life …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, can exacerbate systemic inflammation, leading to atheroma formation and ultimate rupture. 34 Two recent large studies in the United States and Europe also showed that new cases of periodontal disease, not just those preexisting, increase the risk of future cardiovascular events. 18 Several clinical studies suggest that the prevalence of CVD seems to be highest among those individuals in whom periodontitis coexists with elevated C-reactive protein and proinflammatory cytokine levels.…”
mentioning
confidence: 99%